Beneficial Effects of Behavioral Parent Training on Inhibitory Control in Children With Attention-Deficit/Hyperactivity Disorder: A Small-Scale Randomized Controlled Trial - Yao, Akiko; Shimada, Koji; Kasaba, Ryoko; Tomoda, Akemi (Frontiers in Psychiatry, 2022)
The purpose of this study was to examine whether the beneficial effects of behavioral parent training (BPT), as an indirect type of psychosocial treatment, are extended to cognitive manifestations beyond behavioral symptoms of attention-deficit/hyperactivity disorder (ADHD). Although previous studies of community families have shown an association between parenting quality and a child’s cognitive functions, little is known about the effects of BPT on cognitive manifestations in children with ADHD. In this study, we focused on inhibitory control among cognitive domains, which is considered to be the most malleable to direct types of psychosocial treatment for ADHD. We hypothesized that inhibitory control is affected by BPT, which uses parents as the primary agents of change to help their children. Thirty school-age children (6–12 years old) with ADHD and their parents (mothers) participated and were randomly assigned to either the standard BPT or waitlist control group. Using two objective laboratory-based tasks of inhibitory control (i.e., go/no-go and single response selection tasks), we assessed baseline and post-treatment response inhibition to suppress task-irrelevant responses and response selection to select task-relevant responses. In addition to decreased ADHD symptoms and negative parenting, the BPT group exhibited significantly improved performance in the single response selection task, but not in the go/no-go task, compared with the waitlist control group. Although tentative, these findings partially support our hypothesis that BPT has beneficial effects on the cognitive inhibitory control of ADHD, highlighting the potential for supportive environmental modifications to advance cognitive development in children with ADHD.